Care production indicators of nurses in Primary Health Care (Research, Society and Development, 2021)
The work performed by nurses in Primary Care involves care and management approaches, which can make it challenging to maintain care production at satisfactory levels when compared to that of other health professionals. Objective: To characterize the indicators of nurses' care production in relation to the activities of other professionals of the Primary Health Care team in Florianópolis, Santa Catarina (SC), Brazil. Method: Exploratory-descriptive and retrospective study, with a quantitative approach. A database analysis was performed based on computerized records of the institution itself related to the production of workers in the Basic Health Units. Results: Nurses performed most home visits (56.2%), and, together with doctors, the most consultations (83.2%). Dentists (33.3%), psychologists (15.1%) and nurses (15.0%) led group care, while psychologists (25.1%), social workers (19.4%) and nurses (19,3%) participated more frequently in team meetings. It was observed higher mean of nursing consultations in Basic Health Units with seven health teams, and higher mean of technical procedures in Basic Health Units with one health team. Conclusion: Nurses play an important role in providing care to the population, access and resolution, even though they work extensively in team supervision activities.